On noun declension in speeches of Prizren- Timok dialectical areas (Heritage, 2020)
This paper discusses the analytical declension of nouns as one of the most distinctive Balkan’s features in the speeches of Prizren - Timok dialectic areas. First the basic mechanisms of analyticalism were described, and then, based on the material from existing literature of the speeches of this dialectic area, it’s been determined how much analyticalism in these speeches is fully implemented or which case forms show the greatest and which ones the least stability before the analyticalism rush. The conducted analysis indicates to the stability but also to the inconsistency of analyticalism in the analyzed speeches. The rush of analyticalism is largely resisted by the dative, and by the smallest instrumental Also, it is determined that in the analyzed speeches the loss of case forms does not have the same proportion – the analytical declension is more stable in the speeches of southeastern Serbia than in the South Morava’s  speeches in Kosovo and Metohija.
Keywords: declension of nouns, Prizren- Timok-s dialectical area, analyticalism, common case, dependent case forms.